The digital skills conducive to using the Internet and mobile banking services in light of nationwide own research results - Adamek, Jacek; Solarz, Małgorzata (Umiejętności cyfrowe sprzyjające wykorzystaniu usług bankowości internetowej w świetle wyników ogólnopolskich badań własnych, 2020)
The progress and dissemination of information and communication technologies represent an important factor of socio-economic development. Using the opportunities they offer, requires the respective competencies from society. The purpose of the article is to assess the level of digital skills conducive to using the Internet and mobile banking services against the background of the general digital skills presented by Poles. The research methods applied in the article are as follows: the subject literature studies, descriptive and comparative analysis as well as the nationwide survey research conducted in March 2020 using the CAWI method. The analysis and interpretation of the research material allowed the verification of the following research hypothesis – the high level of the general digital skills presented by Poles has a positive impact on the scope of their skills conducive to using both the Internet and mobile banking services
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 5-22